Evaluation of removal efficiency of cu (II) ion by activated carbon prepared from Nirgudi, Mudra and Gliricidia Sipium leaves from their aqueous solution - Bagwan, Mustaqeem Sharif; Patil, Paradip Rajaram (International Journal of Advanced Chemistry, 2014)
Present study deals with the removal of copper ions from aqueous solution by using activated carbon of natural leaves like Nirgudi (NAC), Mudra (MAC) and Gliricidia Sipium (GAC) leaves which is highly efficient, ecofriendly and locally available adsorbents. A series of experiments were conducted in a batch system to evaluate the effect of system variables. The effect of contact time, pH and the initial concentration of copper (II) solution were considered. The results show that the contact time 105 minutes for all adsorbent are sufficient to fit the equilibrium. The optimal adsorption pH for the adsorption of copper (II) ions is 7 for NAC, MAC and 8 for GAC adsorbents. The maximal quantities adsorbed by every adsorbent were 98.63 for NAC, 98.61 for MAC and 98.46 for GAC. Two isotherms models amongst which are Langmuir and Freundlich have been applied to the experimental data. The value of separation factor RL was found to be 0.01847, 0.02506 and 0.04477 for NAC, MAC and GAC respectively suggesting the isotherm to be favorable at the concentration studied. The Langmuir model best described the adsorption of copper (II) ions in aqueous solution by the selected adsorbents.   Keywords: Adsorption isotherms, gliricidia cipium, mudra and, nirgudi.